Proposed Gates of the Arctic National Park, Alaska : final environmental statement - United States. Dept. of the Interior. Alaska Planning Group. ([Washington, D.C.] : The Dept., 1974)
Cover title: Gates of the Arctic National Park. Bibliography: p. 681-686. Mode of access: Internet.